2000
DOI: 10.1088/0305-4470/33/45/103
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational resonance

Abstract: The effect of a high-frequency force on the response of a bistable system to a lowfrequency signal is considered for both the overdamped and weakly damped cases. It is shown that the response can be optimized by an appropriate choice of vibration amplitude. This vibrational resonance displays many analogies to the well known phenomenon of stochastic resonance, but with the vibrational force filling the role usually played by noise. † We use the original definition of SR [4] in terms of signal amplification, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
287
1
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(302 citation statements)
references
References 14 publications
7
287
1
7
Order By: Relevance
“…In addition, although early work on stochastic resonance focused on bi-stable systems excited by white noise, more recent work has shown that similar effects are possible in systems where stochastic noise is replaced with high frequency excitation [10]. This analogous phenomenon occurs when the excitation frequency is well separated from the forcing frequency of the potential well.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, although early work on stochastic resonance focused on bi-stable systems excited by white noise, more recent work has shown that similar effects are possible in systems where stochastic noise is replaced with high frequency excitation [10]. This analogous phenomenon occurs when the excitation frequency is well separated from the forcing frequency of the potential well.…”
Section: Introductionmentioning
confidence: 99%
“…Such external drivings include a chaotic signal [5] or a high-frequency periodic force [6]. In the latter case, the system is driven by a biharmonic signal, consisting of a low-frequency and a high-frequency periodic force.…”
Section: Introductionmentioning
confidence: 99%
“…The terms F i and H are linear in dimensionless random variable ω, i.e., one can indicate a stochastic Langevin's source ω as multiplicative one [30]. The function H in the form (16) guarantees that the trivial value ω ≡ 0 is a singular solution of the dynamic equation (3).…”
Section: Force Field Modelingmentioning
confidence: 99%